2014
DOI: 10.1590/1982-0216201422412
|View full text |Cite
|
Sign up to set email alerts
|

Achados audiológicos em jovens usuários de fones de ouvido

Abstract: Objetivos analisar a relação entre o uso de fones de ouvidos e os comprometimentos auditivos e extra-auditivos provocados pelos tocadores portáteis de música. Métodos a proposta foi coletar dados, por meio de um questionário respondido pelos participantes. Realização dos exames audiométricos: audiometria tonal e vocal; imitânciometria e pesquisa dos reflexos acústicos; emissões otoacústicas transientes e emissões otoacústicas produto de distorção, posteriormente os dados foram comparados entre os indivíduo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 22 publications
1
8
0
9
Order By: Relevance
“…Studies have shown in using headphones, a period of two hours is sufficient for subsequent hearing impairment hearing. It was also found that listening to loud music directly into the ear can damage the sensitive hair cells in the inner ear [2][3][4]6,[28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown in using headphones, a period of two hours is sufficient for subsequent hearing impairment hearing. It was also found that listening to loud music directly into the ear can damage the sensitive hair cells in the inner ear [2][3][4]6,[28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…However, not everyone knows that excessive use of these devices may cause irreversible damage to hearing 1 , in the short or long term 2 . This habit, when frequent, added to the exposure time, the physical characteristics (such as frequency and intensity), and other non-occupational noise at high sound levels, determines the impact on hearing health, and results in a public health problem, which affects most of the world population [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] Indeed, noise is a trademark of modern society 6 and people are generally aware of it, but why is so difficult to change their attitude toward this reality?…”
Section: Introductionmentioning
confidence: 99%